Phytochemical Profiles, DPPH Radical Inhibition Effectiveness, and Cytotoxic Potential of Polyherbal Plants in T47D Cell Line - Wahyuningsih, Nadia; Rahayu, Sri; Rifa'i, Muhaimin (The Journal of Experimental Life Science, 2025)
Breast cancer subtypes include luminal A, luminal B, HER2, triple-negative, and normal-like. Antioxidants, ROS, and cancer have a close relationship. Cancer cells exhibit an elevated ROS level, which can be used for selective cell-based therapeutic targeting. Therefore, developing potential therapeutic potential therapeutic options is crucial. Herbal medicine has gained much interest in treating cancer. Indian jujube (Ziziphus mauritiana), cumin (Nigella sativa), turmeric (Curcuma longa), soursop (Annona muricata), and meniran (Phylanthus niruri) potentially have a role as anticancer agents and were used as alternative medicine. This study aimed to determine the phytochemicals total content, DPPH radical inhibition, and cytotoxicity of the polyherbal plants to the T47D cell line. The antioxidant analysis was conducted using DPPH assay, and the phytochemicals analysis was determined using total flavonoid (TFC), phenolic (TPC), and alkaloid (TAC) content. The cell viability assessment was performed using the WST-1 method. The antioxidant analysis revealed that the IC50 value of polyherbal medicine is 213.65 µg.ml-1. The phytochemical analysis showed that the highest content is the flavonoid compared to others, with a value of 138.986 mgQE.mg-1. Other than that, the cell viability assessment showed that the IC50 of the herbal medicine is 480.8 µg.mL-1. These findings indicated that combining turmeric, cumin, meniran, Indian jujube, and soursop has moderate cytotoxicity against the T47D cell line since it can reduce T47D cell line viability at high doses. Keywords: antioxidant, breast cancer, herbal medicine, phytochemicals, T47D cell line.